Psychometric properties of the Reminiscence Functions Scale for the Portuguese population: a preliminary report. - Gonçalves, D; Guedes, J; Fonseca, A; Martín, I (2010)
The aim of the present study was to assess the psychometric properties of a version in Portuguese of the Reminiscence Functions Scale. Total sample was composed of 628 participants aged between 18 and 92 years, divided into three groups according to their age (18-24 years, n = 249; 26-54 years, n = 174; 55 and older, n = 205). Results indicated a five-factor solution for the Portuguese version of the Reminiscence Functions Scale, which accounted for 54% of the variance with good internal consistency (mean alpha = 0.86). Age and gender differences emerged regarding reminiscence functions. These results demonstrate that, while significant cultural differences exist, the psychometric properties of the Reminiscence Functions Scale are adequate for the Portuguese population.